Determinants for swine mycoplasmal pneumonia reproduction under experimental conditions: A systematic review and recursive partitioning analysis. - Beatriz Garcia-Morante; Joaquim Segalés; Emmanuel Serrano; Marina Sibila (PLoS ONE)
One of the main Mycoplasma hyopneumoniae (M. hyopneumoniae) swine experimental model objectives is to reproduce mycoplasmal pneumonia (MP). Unfortunately, experimental validated protocols to maximize the chance to successfully achieve lung lesions induced by M. hyopneumoniae are not available at the moment. Thus, the objective of this work was to identify those factors that might have a major influence on the effective development of MP, measured as macroscopic lung lesions, under experimental conditions. Data from 85 studies describing M. hyopneumoniae inoculation experiments were compiled by means of a systematic review and analyzed thereafter. Several variables were considered in the analyses such as the number of pigs in the experiment, serological status against M. hyopneumoniae, source of the animals, age at inoculation, type of inoculum, strain of M. hyopneumoniae, route, dose and times of inoculation, study duration and co-infection with other swine pathogens. Descriptive statistics were used to depict M. hyopneumoniae experimental model main characteristics whereas a recursive partitioning approach, using regression trees, assessed the importance of the abovementioned experimental variables as MP triggering factors. A strong link between the time period between challenge and necropsies and lung lesion severity was observed. Results indicated that the most important factors to explain the observed lung lesion score variability were: (1) study duration, (2) M. hyopneumoniae strain, (3) age at inoculation, (4) co-infection with other swine pathogens and (5) animal source. All other studied variables were not relevant to explain the variability on M. hyopneumoniae lung lesions. The results provided in the present work may serve as a basis for debate in the search for a universally accepted M. hyopneumoniae challenge model.